RANK Expression as an Independent Predictor for Response to Neoadjuvant Chemotherapy in Luminal-Like Breast Cancer: A Translational Insight from the GeparX Trial - Link, Theresa; Blohmer, Jens Uwe; Schmitt, Wolfgang D.; Kuhlmann, Jan Dominik; Just, Marianne; Untch, Michael; Stoetzer, Oliver J.; Fasching, Peter; Thill, Marc; Reinisch, Mattea; Schneeweiss, Andreas; Wimberger, Pauline; et al. (Clinical Cancer Research, 2023)
Purpose: The GeparX study investigated whether denosumab as add-on treatment to nab-paclitaxel–based neoadjuvant chemotherapy (NACT) with two different schedules (125 mg/m2 weekly vs. day 1, 8 every 22 days) may increase pathologic complete response (pCR) rate. The addition of denosumab to NACT did not improve pCR rates as recently published. In this study, we investigated whether receptor activator of nuclear factor-kappa B (RANK) expression, as part of the denosumab target pathway: (i) may retrospectively identify a subgroup of patients with additional clinical benefit of denosumab or (ii) may predict response to nab-paclitaxel NACT. Experimental Design: RANK protein was IHC-stained on pre-therapeutic core biopsies from patients of the GeparX study (n ¼ 667) with the antibody RANK/Envision System HRP (DAB) and was analyzed for the percentage of membranous RANK tumor cell staining (>5% RANKhigh vs. ≤5% RANKlow). Results: We could not identify any patient subgroup with differential response under denosumab add-on treatment in patients with RANKhigh expression [139/667, 20.8%; OR, 0.86; 95% confidence interval (CI), 0.44–1.68; P ¼ 0.667] or RANKlow expression (528/667 (79.2%) OR, 1.10; 95% CI, 0.78–1.56; P ¼ 0.589; Pinteraction ¼ 0.528). However, the pCR rate was higher in the RANKhigh subgroup compared with RANKlow (50% vs. 39%; OR, 1.52; 95% CI, 1.04–2.21; P ¼ 0.037). RANK expression constituted an independent predictor of response to NACT frequently in patients with luminal-like subtype (HRþ/HER2−; OR, 2.98; 95% CI, 1.30–6.79; P ¼ 0.010). No predictive value of RANK expression among the different nab-paclitaxel regimens was observed. Conclusion: We report RANK expression to be an independent predictive biomarker for response to NACT in patients with luminal-like breast cancer.
CRIS-Team Scopus Importer:2023-12-08